2006
DOI: 10.1128/jvi.80.2.854-865.2006
|View full text |Cite
|
Sign up to set email alerts
|

R5 Variants of Human Immunodeficiency Virus Type 1 Preferentially Infect CD62LCD4+T Cells and Are Potentially Resistant to Nucleoside Reverse Transcriptase Inhibitors

Abstract: The persistence of human immunodeficiency virus type 1 (HIV-1) in memory CD4؉ T cells is a major obstacle to the eradication of the virus with current antiretroviral therapy. Here, we investigated the effect of the activation status of CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…We let n t and m t represent the total numbers (i.e., activated + non-activated) of naïve and memory CD4 + T cells, respectively. Because naïve and memory cell counts are initially similar and because R5 virus disproportionately depletes memory CD4 + T cells [40,41], we assume that n t > m t during R5 infection, implying: mt(1am)<nt(1an)…”
Section: Resultsmentioning
confidence: 99%
“…We let n t and m t represent the total numbers (i.e., activated + non-activated) of naïve and memory CD4 + T cells, respectively. Because naïve and memory cell counts are initially similar and because R5 virus disproportionately depletes memory CD4 + T cells [40,41], we assume that n t > m t during R5 infection, implying: mt(1am)<nt(1an)…”
Section: Resultsmentioning
confidence: 99%
“…Memory CD4 + T cells separated from PBMC by means of a memory CD4 + T cell isolation kit (Miltenyi Biotech, France) were cultured at the concentration of 10 6 cells per milliliter of RPMI 1640 supplemented with 200-U/ml recombinant IL-2 (Chiron), 15% fetal calf serum, and antibiotics in duplicate in a total volume of 100 µl in the presence of HIV-1-reactivating agents. After a 3-day stimulation, CD4 + T cells were 10-fold serially diluted and co-cultured with PHA-activated CD4 + T cells from an allogeneic healthy donor, as described in detail previously [71] . HIV-1 replication was followed by determination of p24 in the cell-free supernatant by means of Genetic System HIV Ag EIA (BioRad France, Marnes la Coquettes).…”
Section: Methodsmentioning
confidence: 99%
“…Also, activated and previously activated T cells express both CCR5 and CXCR4 (5,55,58), providing a potential source of mixing of R5 and X4 variants. There is evidence to suggest that the pool of cells supporting the bulk of virus replication is not homogeneous in its susceptibility to infection by X4 and R5 variants (22) and that X4 and R5 variants may be differentially affected by antiretroviral therapy (22,66). However, we found no difference in the decay rates of X4 and R5 variants upon initiation of therapy, and the decay rates of these variants are within the range reported in other studies for the first phase of decay, presumably reflecting the life spans of the activated memory cells supporting ϳ99% of the virus population (34,49,62,63,96).…”
Section: Discussionmentioning
confidence: 99%
“…These and subsequent studies (4,49,62,63) suggested that the average life span of infected cells that produce 99% or more of the bulk HIV-1 population in the peripheral blood is short, with a half-life of 1 to 2 days, presumably reflecting the life span of activated T cells, whereas cells producing 1% or less of the population have a half-life measured in weeks, illustrated by a biphasic decay curve. However, the bulk HIV-1 RNA decay rate of the first phase may oversimplify the dynamics of the underlying viral genetic subpopulations because this rate may represent an average without accounting for possible moderate differences between decay rates of coexisting variants, as might be the case for variants infecting cellular subsets in different stages of maturation or activation (22,59,100). Based on this model, two or more coexisting viral populations with the same rates of decay during HAART could be presumed to be produced by the same cellular subset or, at minimum, two or more subsets with the same turnover rate.…”
mentioning
confidence: 99%